Acute Coronary Syndrome In HIV Naïve Patient With Low CD4 Count And No Other Significant Risk Factors: Case Report And Literature Review - Fanari, Zaher (Open J Clin Med Case Rep, 2015)
Coronary artery disease (CAD) has become the leading cause of mortality in patients with Human Immunodeficiency Virus (HIV). The typical HIV-infected patient presenting with acute coronary syndrome (ACS) is a man in his mid to late 40s. The most common presentation is an acute myocardial infarction (MI), most often with ST segment elevation. Coronary anatomy seems to be variable, with some studies showing a higher prevalence of single-vessel disease and others showing a higher prevalence of 2- and 3-vessel disease than in controls not infected with HIV.